New White Method of Parameters and Reliability Estimation for Transmuted Power Function Distribution - Makki A. Mohammed Salih; Jaafer Hmood Eidi (مجلة بغداد للعلوم, 2022)
In this paper, an estimate has been made for parameters and the reliability function for Transmuted power function (TPF) distribution through using some estimation methods as proposed new technique for white, percentile, least square, weighted least square and modification moment methods. A simulation was used to generate random data that follow the (TPF) distribution on three experiments (E1 , E2 , E3)  of the real values of the parameters, and with sample size (n=10,25,50 and 100) and iteration samples (N=1000), and taking reliability times (0< t < 0) . Comparisons have been made between the obtained results from the estimators using mean square error (MSE). The results showed the percentile estimator is the best in (E1, E2)  but modification moment is the best in (E3) .